Effects of dietary starch sources on growth, nutrient utilization and liver histology of juvenile tinfoil barb (Barbonymus schwanenfeldii, Bleeker 1853) - Mohamed Nafees, Mohamed Salihu; Kamarudin, Mohd Salleh; Karim, Murni; Hassan, Mohd Zafri; De Cruz, Clement Roy (Elsevier, 2022)
Aquafeeds with optimum digestible starch levels provide nutritional, economic, and environmental benefits in aquaculture. Tinfoil barb juveniles can optimally utilize 19.25% dietary corn starch, but their ability to use commonly available starch sources has not been explored. This study aimed to compare the effects of starch sources on fish growth, nutrient retention, intestinal α-amylase activity and liver histology. Five experimental diets with approximately 45% crude protein and 17.5 kJ g–1 gross energy were prepared using native corn, sago and tapioca starches and taro and wheat flours. Each diet was randomly allocated to triplicate groups of 20 fish (3.34 ± 0.12 g) and feeding was done for eight weeks. Results revealed that weight gain and specific growth rate of fish did not differ among the starch sources. However, compared to corn starch, dietary taro flour increased daily feed intake of fish whereas wheat flour decreased it (P < 0.05). Fish fed dietary corn and tapioca starches showed lower feed conversion ratio and higher protein efficiency than those fed taro flour (P < 0.05). Protein and energy retention were lower in taro group compared to corn group whereas lipid retention was lower in taro and wheat groups than corn and tapioca groups (P < 0.05). Midgut α-amylase activity was higher in fish fed sago and tapioca than those fed taro and wheat flours (P < 0.05). Hepatocyte was smaller in taro group than fish fed other diets while its nucleus was smaller in wheat group compared to corn group (P < 0.05). Lower performance in flour-based diet groups could be attributed to flour properties. Overall performance of sago and wheat groups was comparable to both corn and taro groups. In conclusion, tinfoil barb juveniles could better utilize corn and tapioca starches but not taro flour. The findings can extend appropriate use of starch in aquafeeds to sustain future aquaculture.